PERTUMBUHAN KAPANG Monascus purpureus, Aspergillus flavus DAN Penicillium SP PADA MEDIA BERAS, JAGUNG DAN KOMBINASI BERAS JAGUNG - Retnowati, Yuliana; D.Uno, Wirnangsi; Kumaji, Syam; Humokor, Yulianti (Sainstek, 2010)
The object of this study was to know the growth of Monascus purpureus, Aspergillus flavus and Penicillium sp at the rice, corn and rice-corn combination media which based on the description method. The observation of study was done for sixteen days while the increasement of percentage of myselium mass fungus as indicator of the growth. The result of study shown that the growth of Monascus purpureus, Aspergillus flavus and Penicillium sp at each of the rice, corn and ricecorn combination media was dominated by Aspergillis flavus and their forming amensalysm symbiosis. Keywords : growth, Monascus purpureus, Aspergillus flavus, Penicillium sp.